Energy deficit required for rapid weight loss in elite collegiate wrestlers - Kondo, E.; Sagayama, H.; Yamada, Y.; Shiose, K.; Osawa, T.; Motonaga, K.; Ouchi, S.; Kamei, A.; Nakajima, K.; Higaki, Y.; Tanaka, H.; Takahashi, H.; et al. (Nutrients, 2018)
To determine energy density for rapid weight loss (RWL) of weight-classified sports, eight male elite wrestlers were instructed to lose 6% of body mass (BM) within 53 h. Energy deficit during the RWL was calculated by subtracting total energy expenditure (TEE) determined using the doubly labeled water method (DLW) from energy intake (EI) assessed with diet records. It was also estimated from body composition change estimated with the four-component model (4C) and other conventional methods. BM decreased significantly by 4.7 ± 0.5 kg (6.4 ± 0.5%). Total body water loss was the major component of the BM loss (71.0 ± 7.6%). TEE was 9446 ± 1422 kcal, and EI was 2366 ± 1184 kcal during the RWL of 53-h; therefore, the energy deficit was 7080 ± 1525 kcal. Thus, energy density was 1507 ± 279 kcal/kg BM during the RWL, comparable with values obtained using the 4C, three-component model, dual energy X-ray absorptiometry, and stable isotope dilution. Energy density for RWL of wrestlers is lower than that commonly used (7400 or 7700 kcal/kg DeltaBM). Although RWL is not recommended, we propose that commonly practiced extreme energy restriction such as 7400 or 7700 kcal/kg DelteBM during RWL appears to be meaningless